Analysis Reception Cancel Culture Kpop Idol - Putri, Dea Amanda; Sari Kusuma, Rina (Jogjakarta Communication Conference (JCC), 2025)
Social norms are shared rules that dictate acceptable behavior within a specific group, leading to social sanctions such as ostracism or reprimands. Online, these norms can manifest as Cancel Culture, commonly associated with boycotting individuals, brands, or companies for perceived offensive behavior. In the case of celebrities, this often involves fans calling for boycotts due to problematic actions. This research explores how audiences interpret media messages, guided by Stuart Hall's reception analysis theory, which acknowledges diverse interpretations based on social and cultural backgrounds. Specifically, it examines audience responses to the Moon Taeil controversy. Findings show that many fans support the cancellation movement against Moon Taeil, viewing it as a way to stand in solidarity with victims of sexual violence. This attitude reflects their experiences and loyalty to the NCT group. Social media discussions highlight the substantial impact of fan opinions on the issue, and official statements from SM Entertainment shape public understanding. Ultimately, supporting Cancel Culture is seen by many fans as the right course of action in response to the scandal.